Molding resin composition and electronic component device
By adding porous polymer particles and optimizing the component ratio to the resin composition for forming, the dielectric loss tangent is reduced, and the problem of low communication efficiency of existing resin compositions in high-frequency environments is solved. It is suitable for high-frequency devices. and sealing materials for encapsulating antennas.
Patent Information
- Application Number
- CN202380037616.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-11-13
- Publication Date
- 2024-12-24
AI Technical Summary
The conventional resin composition for forming is difficult to meet the demand for high frequency due to the high tangent of the dielectric loss in a high frequency environment.
Using a resin composition for forming a forming process including epoxy resin, active ester compound hardener, inorganic filler and porous polymer particles, the relative dielectric constant and dielectric are reduced by adjusting the component ratio and the hollow rate of the porous polymer particles. Loss tangent.
It realizes the reduction of dielectric loss tangent in high-frequency environments and improves communication efficiency. It is suitable for sealing materials for high-frequency devices and packaged antennas.
Smart Images

Figure BDA0005111439360000061 
Figure BDA0005111439360000071 
Figure BDA0005111439360000072
Abstract
Description
Technical Field
[0001] The present disclosure relates to a molding resin composition and an electronic component device. Background Art
[0002] With the recent demand for electronic devices to be more functional, thin and small, the high-density integration and mounting of electronic parts have been promoted, and the number of semiconductor packages used in these electronic devices has increased compared to the past, and the miniaturization has been promoted. Furthermore, the high frequency of radio waves used for communication in electronic devices is also being promoted.
[0003] For example, Patent Documents 1 and 2 propose a high dielectric constant resin composition for use in sealing semiconductor elements in order to reduce the size of semiconductor packages and cope with high frequencies.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-036410
[0007] Patent Document 2: Japanese Patent Application Publication No. 2018-141052 Summary of the invention
[0008] Problems to be solved by the invention
[0009] As the material of the electronic parts such as the sealing semiconductor element, for example, the molding resin composition comprising epoxy resin, hardener and inorganic filler can be cited. As the molding resin composition, if the material with high dielectric loss tangent is used, the transmission signal is converted into heat due to dielectric loss, and the communication efficiency is easily reduced. Here, the amount of dielectric loss generated by the electric wave sent for communication is expressed as the product of the square root of the frequency, the relative dielectric constant and the dielectric loss tangent. The transmission signal is easily converted into heat in proportion to the frequency. Especially in recent years, in order to cope with the increase of the number of channels accompanying the diversified information, the electric wave used in the communication is high-frequencyized. In order to suppress dielectric loss, a molding resin composition capable of molding a hardened object with low relative dielectric constant is sought.
[0010] The present disclosure has been made in view of the above-mentioned conventional circumstances, and an object of the present disclosure is to provide a molding resin composition capable of molding a cured product having a low relative dielectric constant, and an electronic component device using the same.
[0011] Technical means of solving problems
[0012] The specific means for achieving the above-mentioned objects are as follows.
[0013] <1> A molding resin composition comprising: an epoxy resin; a hardener comprising an active ester compound; an inorganic filler; and porous polymer particles.
[0014] <2> The molding resin composition according to <1>, wherein the porous polymer particles include a core having a porous shape and a shell covering at least a portion of the core.
[0015] <3> The molding resin composition according to <1> or <2>, wherein the porous polymer particles include a core having a porous shape, and the core includes at least one polymer selected from the group consisting of a (meth)acrylic polymer, an olefin polymer, a styrene polymer, and a urethane polymer.
[0016] <4> The molding resin composition according to any one of <1> to <3>, wherein the content of the porous polymer particles is 5% by volume to 50% by volume based on the total amount of the inorganic filler and the porous polymer particles.
[0017] <5> The molding resin composition according to any one of <1> to <4>, wherein the content of the porous polymer particles is 3% by volume to 40% by volume based on the total amount of the molding resin composition.
[0018] <6> The molding resin composition according to any one of <1> to <5>, wherein the porous polymer particles are thermosetting.
[0019] <7> The molding resin composition according to any one of <1> to <6>, which is used for a high-frequency device.
[0020] <8> The molding resin composition according to <7>, which is used for sealing electronic components in high-frequency devices.
[0021] <9> The molding resin composition according to <7>, which is used for encapsulating an antenna.
[0022] <10> An electronic component device, comprising:
[0023] Supporting members;
[0024] electronic components, disposed on the supporting member; and
[0025] A cured product of the molding resin composition according to any one of <1> to <9> for sealing the electronic component.
[0026] <11> The electronic component device according to <10>, wherein the electronic component includes an antenna.
[0027] Effects of the Invention
[0028] According to the present disclosure, it is possible to provide a molding resin composition capable of molding a cured product having a low relative dielectric constant, and an electronic component device using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] [ Figure 1 ] Figure 1 This is a graph showing SS curves of elongation at break and flexural strength obtained using the molding resin compositions of the respective Examples and Comparative Examples.
[0030] [ Figure 2 ] Figure 2 It is a graph showing changes in viscoelastic properties obtained using a composition including filler 5 . DETAILED DESCRIPTION
[0031] Hereinafter, the embodiments of the present disclosure are described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the constituent components (including component processes, etc.) are not required except for the cases specifically indicated. The same is true for numerical values and their ranges, which do not limit the present disclosure.
[0032] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.
[0033] In the present disclosure, in a numerical range represented by “to”, numerical values described before and after including “to” are respectively regarded as the minimum value and the maximum value.
[0034] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiment.
[0035] In the present disclosure, each component may include multiple equivalent substances. When multiple substances equivalent to each component exist in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the multiple substances present in the composition.
[0036] In the present disclosure, particles corresponding to each component may include multiple types of particles. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition unless otherwise specified.
[0037] <Molding resin composition>
[0038] The molding resin composition disclosed herein comprises: an epoxy resin; a curing agent comprising an active ester compound; an inorganic filler; and porous polymer particles. Thus, the molding resin composition disclosed herein can be molded into a cured product having a low relative dielectric constant.
[0039] Hereinafter, each component constituting the molding resin composition will be described. The molding resin composition of the present disclosure contains at least an epoxy resin, a hardener, an inorganic filler, and porous polymer particles, and may contain other components as necessary.
[0040] (Epoxy resin)
[0041] The molding resin composition of the present disclosure contains an epoxy resin. The type of the epoxy resin is not particularly limited as long as it has an epoxy group in the molecule.
[0042] From the viewpoints of strength, fluidity, heat resistance, moldability, etc., the mass ratio of the epoxy resin in the entire molding resin composition is preferably 0.5 mass % to 30 mass %, more preferably 2 mass % to 20 mass %, and further preferably 3.5 mass % to 13 mass %.
[0043] Examples of the epoxy resin include: novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenolic compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aliphatic aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde under an acidic catalyst to obtain a novolac resin, and then epoxidizing the novolac resin; and novolac-type epoxy resins (phenol novolac-type epoxy resins, o-cresol novolac-type epoxy resins, etc.) obtained by condensing or co-condensing the phenolic compound with an aromatic aldehyde compound such as benzaldehyde and salicylaldehyde under an acidic catalyst to obtain a triphenylmethane-type phenol resin, and then epoxidizing the triphenylmethane-type phenol resin. triphenylmethane epoxy resin obtained by epoxidation; copolymerized epoxy resin obtained by epoxidizing a novolac resin obtained by co-condensing the phenol compound and naphthol compound with an aldehyde compound under an acidic catalyst; diphenylmethane epoxy resin as a diglycidyl ether of bisphenol A, bisphenol F, etc.; biphenyl epoxy resin as a diglycidyl ether of an alkyl-substituted or unsubstituted biphenol; styrene epoxy resin as a diglycidyl ether of a styrene-based phenol compound; epoxy resin as a glycidyl ether of alcohols such as butanediol, polyethylene glycol, and polypropylene glycol; glycidyl ester epoxy resin as a glycidyl ester of a polycarboxylic acid compound such as phthalic acid, isophthalic acid, and tetrahydrophthalic acid ; Glycidylamine epoxy resins obtained by replacing the active hydrogen bonded to the nitrogen atom of aniline, diaminodiphenylmethane, isocyanuric acid, etc. with a glycidyl group; dicyclopentadiene epoxy resins obtained by epoxidizing a co-condensation resin of dicyclopentadiene and a phenol compound; alicyclic epoxy resins such as diepoxy vinylcyclohexene, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 2-(3,4-epoxy)cyclohexyl-5,5-spiro(3,4-epoxy)cyclohexane-m-dioxane obtained by epoxidizing an olefin bond in a molecule; p-xylene-modified epoxy resins as glycidyl ethers of p-xylene-modified phenol resins; m-xylene-modified epoxy resins as glycidyl ethers of m-xylene-modified phenol resins; esters; terpene-modified epoxy resins as glycidyl ethers of terpene-modified phenol resins; dicyclopentadiene-modified epoxy resins as glycidyl ethers of dicyclopentadiene-modified phenol resins; cyclopentadiene-modified epoxy resins as glycidyl ethers of cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified epoxy resins as glycidyl ethers of polycyclic aromatic ring-modified phenol resins; naphthalene-type epoxy resins as glycidyl ethers of phenol resins containing naphthalene rings; halogenated phenol novolac-type epoxy resins; hydroquinone-type epoxy resins; trimethylolpropane-type epoxy resins; linear aliphatic epoxy resins obtained by oxidizing olefin bonds using peracids such as peracetic acid; aralkyl-type epoxy resins obtained by epoxidizing aralkyl-type phenol resins such as phenol aralkyl resins and naphthol aralkyl resins, etc.Furthermore, epoxides of acrylic resins and the like can also be mentioned as epoxy resins. The epoxy resins may be used alone or in combination of two or more.
[0044] The epoxy resin may include at least one of triphenylmethane epoxy resin, o-cresol novolac epoxy resin, biphenyl aralkyl epoxy resin and biphenyl epoxy resin, and may include triphenylmethane epoxy resin and biphenyl epoxy resin, or triphenylmethane epoxy resin and o-cresol novolac epoxy resin.
[0045] The epoxy equivalent (molecular weight / number of epoxy groups) of the epoxy resin is not particularly limited. From the viewpoint of balancing various properties such as moldability, reflow resistance, and electrical reliability, the epoxy equivalent of the epoxy resin is preferably 100 g / eq to 1000 g / eq, and more preferably 150 g / eq to 500 g / eq.
[0046] The epoxy equivalent of the epoxy resin is set to a value measured by a method in accordance with Japanese Industrial Standards (JIS) K 7236:2009.
[0047] When the epoxy resin is solid, the softening point or melting point of the epoxy resin is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the epoxy resin is preferably 40°C to 180°C, and from the viewpoint of operability during preparation of the molding resin composition, it is more preferably 50°C to 130°C.
[0048] The melting point or softening point of the epoxy resin is defined as a value measured by differential scanning calorimetry (DSC) or a method (ring and ball method) in accordance with JIS K 7234:1986.
[0049] (Hardener)
[0050] The molding resin composition of the present disclosure contains a curing agent containing an active ester compound.
[0051] The molding resin composition may contain only one curing agent or two or more. For example, the curing agent may contain only one active ester compound or two or more active ester compounds, or may contain an active ester compound and other curing agents (eg, phenol curing agents).
[0052] When a phenol hardener is used as a hardener for an epoxy resin, for example, a secondary hydroxyl group is generated in the reaction between the epoxy resin and the phenol hardener. In contrast, when an active ester compound is used as a hardener for an epoxy resin, an ester group is generated in the reaction between the epoxy resin and the active ester compound instead of the secondary hydroxyl group. Since the ester group has a lower polarity than the secondary hydroxyl group, it is speculated that the molding resin composition containing the active ester compound as a hardener can suppress the dielectric loss tangent and relative dielectric constant of the hardened material to be lower than the molding resin composition containing only a hardener that generates a secondary hydroxyl group as a hardener.
[0053] In addition, the polar groups in the cured product increase the water absorption of the cured product. By using an active ester compound as a curing agent, the concentration of polar groups in the cured product can be suppressed, and the water absorption of the cured product can be suppressed. In addition, it is speculated that by suppressing the water absorption of the cured product, that is, suppressing the content of H2O as a polar molecule, the dielectric loss tangent and relative dielectric constant of the cured product can be suppressed to a lower level.
[0054] -Active ester compound-
[0055] Here, the active ester compound refers to a compound having one or more ester groups reactive with an epoxy group in one molecule and having a curing effect on the epoxy resin.
[0056] The active ester compound is not particularly limited in type if it is a compound having one or more ester groups that react with an epoxy group in the molecule. Examples of the active ester compound include phenol ester compounds, thiophenol ester compounds, N-hydroxylamine ester compounds, and esters of heterocyclic hydroxy compounds. These active ester compounds may be used alone or in combination of two or more.
[0057] Examples of the active ester compound include ester compounds obtained from at least one of an aliphatic carboxylic acid and an aromatic carboxylic acid and at least one of an aliphatic hydroxyl compound and an aromatic hydroxyl compound. An ester compound using an aliphatic compound as a polycondensation component tends to have excellent compatibility with epoxy resins due to the presence of an aliphatic chain. An ester compound using an aromatic compound as a polycondensation component tends to have excellent heat resistance due to the presence of an aromatic ring.
[0058] As specific examples of active ester compounds, aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups can be cited. Among them, aromatic carboxylic acid components obtained by replacing 2 to 4 hydrogen atoms of aromatic rings such as benzene, naphthalene, biphenyl, diphenylpropane, diphenylmethane, diphenyl ether, diphenylsulfonic acid with carboxyl groups, monohydric phenols obtained by replacing 1 hydrogen atom of the aromatic ring with hydroxyl groups, and mixtures of polyhydric phenols obtained by replacing 2 to 4 hydrogen atoms of the aromatic ring with hydroxyl groups as raw materials are preferably used. Aromatic esters obtained by condensation reaction of aromatic carboxylic acids and phenolic hydroxyl groups. That is, aromatic esters having structural units derived from the aromatic carboxylic acid components, structural units derived from the monohydric phenols, and structural units derived from the polyhydric phenols are preferably used.
[0059] Specific examples of active ester compounds include phenol resins having a molecular structure in which a phenol compound is linked via an aliphatic cyclic hydrocarbon group, as described in Japanese Patent Laid-Open No. 2012-246367, and active ester resins having a structure obtained by reacting an aromatic dicarboxylic acid or a halide thereof with an aromatic monohydroxy compound. The active ester resin is preferably a compound represented by the following structural formula (1).
[0060] [Chemistry 1]
[0061]
[0062] In the structural formula (1), R 1 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group; X is an unsubstituted benzene ring, an unsubstituted naphthalene ring, a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms, or a biphenyl group; Y is a benzene ring, a naphthalene ring, or a benzene ring or a naphthalene ring substituted with an alkyl group having 1 to 4 carbon atoms; k is 0 or 1; and n represents the average number of repetitions and is 0 to 5.
[0063] Specific examples of the compound represented by the structural formula (1) include the following exemplary compounds (1-1) to (1-10): t-Bu in the structural formula is a tert-butyl group.
[0064] [Chemistry 2]
[0065]
[0066] [Chemistry 3]
[0067]
[0068] Other specific examples of the active ester compound include a compound represented by the following structural formula (2) and a compound represented by the following structural formula (3) described in JP-A-2014-114352.
[0069] [Chemistry 4]
[0070]
[0071] In the structural formula (2), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0072] In the structural formula (3), R 1 and R 2 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms, Z is an ester-forming structural site (z1) or a hydrogen atom (z2) selected from the group consisting of an unsubstituted benzoyl group, an unsubstituted naphthoyl group, a benzoyl group or naphthoyl group substituted with an alkyl group having 1 to 4 carbon atoms, and an acyl group having 2 to 6 carbon atoms, and at least one of Z is an ester-forming structural site (z1).
[0073] Specific examples of the compound represented by the structural formula (2) include the following exemplary compounds (2-1) to (2-6).
[0074] [Chemistry 5]
[0075]
[0076] Specific examples of the compound represented by the structural formula (3) include the following exemplary compounds (3-1) to (3-6).
[0077] [Chemistry 6]
[0078]
[0079] As the active ester compound, commercially available products can also be used. As commercially available products of the active ester compound, active ester compounds containing a dicyclopentadiene-type diphenol structure include "EXB9451", "EXB9460", "EXB9460S", and "HPC-8000-65T" (manufactured by DIC Co., Ltd.); active ester compounds containing an aromatic structure include "EXB9416-70BK", "EXB-8", and "EXB-9425" (manufactured by DIC Co., Ltd.); active ester compounds containing acetylated products of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Co., Ltd.); active ester compounds containing benzoylated products of phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Co., Ltd.), etc.
[0080] The ester equivalent (molecular weight / number of ester groups) of the active ester compound is not particularly limited, but is preferably 150 g / eq to 400 g / eq, more preferably 170 g / eq to 300 g / eq, and even more preferably 200 g / eq to 250 g / eq from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.
[0081] The ester equivalent of the active ester compound is set to a value measured by a method in accordance with JIS K 0070:1992.
[0082] The curing agent may also contain other curing agents other than the active ester compound. Examples of other curing agents include phenol curing agents, amine curing agents, acid anhydride curing agents, polythiol curing agents, polyaminoamide curing agents, isocyanate curing agents, and blocked isocyanate curing agents. Among them, phenol curing agents are preferred.
[0083] The molding resin composition may contain only one type of other curing agent, or may contain two or more types.
[0084] -Phenol Hardener-
[0085] Specific examples of the phenol curing agent include: polyphenol compounds such as resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols; novolac-type phenol resins obtained by condensing or co-condensing at least one phenolic compound selected from the group consisting of phenol compounds such as phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, aminophenol, and naphthol compounds such as α-naphthol, β-naphthol, and dihydroxynaphthalene with an aldehyde compound such as formaldehyde, acetaldehyde, and propionaldehyde in the presence of an acid catalyst; and polyphenol compounds such as polyphenols obtained by condensing or co-condensing the phenolic compounds with dimethoxy-p-xylene, bis(methoxymethyl)biphenyl, and the like. Synthetic aralkyl phenol resins such as phenol aralkyl resins and naphthol aralkyl resins; p-xylene-modified phenol resins and m-xylene-modified phenol resins; melamine-modified phenol resins; terpene-modified phenol resins; dicyclopentadiene-type phenol resins and dicyclopentadiene-type naphthol resins synthesized by copolymerizing the above-mentioned phenolic compounds with dicyclopentadiene; cyclopentadiene-modified phenol resins; polycyclic aromatic ring-modified phenol resins; biphenyl-type phenol resins; triphenylmethane-type phenol resins obtained by condensing or co-condensing the above-mentioned phenolic compounds with aromatic aldehyde compounds such as benzaldehyde and salicylaldehyde under an acidic catalyst; phenol resins obtained by copolymerizing two or more of these, etc. These phenolic hardeners may be used alone or in combination of two or more.
[0086] The hydroxyl equivalent of the phenol curing agent is not particularly limited, but is preferably 70 to 1000 g / eq, more preferably 80 to 500 g / eq, from the viewpoint of balancing various properties such as formability, reflow resistance, and electrical reliability.
[0087] The hydroxyl equivalent of the phenol curing agent is set to a value measured by a method in accordance with JIS K 0070:1992.
[0088] The equivalent ratio of the epoxy resin to the hardener, i.e., the ratio of the number of functional groups in the hardener (preferably the number of ester groups or the total number of ester groups and hydroxyl groups) to the number of functional groups in the epoxy resin (preferably the number of epoxy groups) (the number of functional groups in the hardener / the number of functional groups in the epoxy resin) is not particularly limited. From the viewpoint of suppressing the amount of each unreacted component, it is preferably 0.5 to 2.0, and more preferably 0.6 to 1.3. From the viewpoint of formability and reflow resistance, it is further preferably 0.8 to 1.2.
[0089] When an active ester compound and a phenol curing agent are used in combination as the curing agent, the molar ratio of the ester group contained in the active ester compound to the phenolic hydroxyl group contained in the phenol curing agent (ester group / phenolic hydroxyl group) is preferably 9 / 1 to 1 / 9, more preferably 8 / 2 to 2 / 8, and further preferably 3 / 7 to 7 / 3.
[0090] When an active ester compound and another hardener (preferably a phenol hardener) are used together as a hardener, the mass ratio of the active ester compound in the total amount of the active ester compound and the other hardener (preferably a phenol hardener) is preferably 40 mass % to 90 mass %, more preferably 50 mass % to 80 mass %, and even more preferably 55 mass % to 70 mass %, from the viewpoint of achieving excellent flexural strength of the molding resin composition after hardening and suppressing the dielectric loss tangent of the hardened material to be low.
[0091] The softening point or melting point of the active ester compound as a hardener and other hardeners such as a phenol hardener used as needed is not particularly limited. From the viewpoint of moldability and reflow resistance, the softening point or melting point of the hardener is preferably 40°C to 180°C, and from the viewpoint of operability during the production of the molding resin composition, it is more preferably 50°C to 130°C.
[0092] The melting point or softening point of the curing agent is set to a value measured in the same manner as the melting point or softening point of the epoxy resin.
[0093] (Inorganic filler)
[0094] The molding resin composition disclosed in the present invention contains an inorganic filler. The type of inorganic filler is not particularly limited. Specifically, inorganic materials such as fused silica, crystalline silica, glass, aluminum oxide, aluminum nitride, boron nitride, talc, clay, mica, titanium compounds such as calcium titanate, etc. can be listed. Inorganic fillers with flame retardant effects can also be used. As inorganic fillers with flame retardant effects, composite metal hydroxides such as aluminum hydroxide, magnesium hydroxide, composite hydroxides of magnesium and zinc, zinc borate, etc. can be listed.
[0095] In inorganic filler, with respect to the viewpoint of reducing the linear expansion coefficient, preferably silicon dioxide such as fused silica, with respect to the viewpoint of high thermal conductivity, preferably aluminum oxide. With respect to the viewpoint of further reducing the dielectric loss tangent, preferably boron nitride. Inorganic filler can be used alone or in combination of two or more. As the form of inorganic filler, powder, beads, fibers, etc., which are sphericalized powders, can be listed.
[0096] The average particle size of the inorganic filler is not particularly limited. For example, the volume average particle size is preferably 0.2 μm to 50 μm, and more preferably 0.5 μm to 30 μm.
[0097] If the volume average particle size is more than 0.2 μm, there is a tendency that the viscosity of the molding resin composition is further suppressed. If the volume average particle size is less than 50 μm, there is a tendency that the filling property of the narrow gap is further improved. The volume average particle size of the inorganic filler refers to the value obtained by measuring the particle size distribution of the laser diffraction scattering method as the volume average particle size (D50).
[0098] The volume average particle size of the inorganic filler in the molding resin composition or its cured product can be measured by a known method. As an example, an organic solvent, nitric acid, aqua regia, etc. are used to extract the inorganic filler from the molding resin composition or the cured product, and the dispersion is fully dispersed using an ultrasonic disperser, etc., and a dispersion is prepared. The volume average particle size of the inorganic filler can be measured according to the particle size distribution of the volume basis obtained by using the dispersion and measuring the particle size distribution of the laser diffraction scattering method particle size distribution measuring device. Alternatively, the volume average particle size of the inorganic filler can be measured according to the particle size distribution of the volume basis obtained by burying the cured product in a transparent epoxy resin, etc. and grinding the obtained section using a scanning electron microscope. . And then, it is also possible to use a focused ion beam (Focused Ion Beam, FIB) device (focused ion beam scanning electron microscope (Scanning Electron Microscope, SEM)) etc. to continuously observe the two-dimensional section of the cured product and perform three-dimensional structural analysis and measure.
[0099] From the viewpoint of the fluidity of the molding resin composition, the particle shape of the inorganic filler is preferably spherical rather than square, and the particle size distribution of the inorganic filler is preferably distributed over a wide range.
[0100] From the viewpoint of low relative dielectric constant and high fracture energy of the cured product, the total content of the inorganic filler contained in the molding resin composition is preferably more than 40 volume %, more preferably more than 50 volume %, further preferably more than 50 volume % and less than 80 volume %, and particularly preferably 55 volume % to 70 volume % relative to the total amount of the molding resin composition.
[0101] The content (volume %) of the inorganic filler in the molding resin composition can be determined by the following method.
[0102] A thin slice sample of a cured product of the molding resin composition is photographed using a scanning electron microscope (SEM). An arbitrary area S is determined in the SEM image, and the total area A of the inorganic filler contained in the area S is obtained. The value obtained by dividing the total area A of the inorganic filler by the area S is converted into a percentage (%), and the value is set as the content (volume %) of the inorganic filler in the molding resin composition.
[0103] The area S is set to be sufficiently large relative to the size of the inorganic filler. For example, it is set to be large enough to contain 100 or more inorganic fillers. The area S may also be the total of a plurality of cut surfaces.
[0104] Inorganic fillers may have a ratio deviation in the gravity direction when the molding resin composition is cured. In such a case, when photographing with SEM, the entire hardened material in the gravity direction is photographed, and the area S including the entire hardened material in the gravity direction is determined.
[0105] (Porous polymer particles)
[0106] The molding resin composition disclosed herein contains porous polymer particles. By replacing part of the inorganic filler with the porous polymer particles, the relative dielectric constant can be reduced while maintaining a low dielectric loss tangent.
[0107] The porous polymer particles are not particularly limited as long as they are porous particles containing a polymer. The porous polymer particles preferably contain at least one polymer selected from the group consisting of a (meth)acrylic polymer, an olefin polymer, a styrene polymer, and a urethane polymer. From the viewpoint that the dimensional change of the molded article containing the molding resin composition before and after curing is easily reduced, the porous polymer particles preferably contain a styrene polymer.
[0108] The porous polymer particles may include a core with a porous shape and a shell covering at least a portion of the core. The core with a porous shape is located on the surface through a portion of pores and produces a concavo-convex shape on its surface. The core is covered by the shell, and at least a portion of the concavo-convex shape is covered by the shell layer. Therefore, there is a tendency that the surface of the porous polymer particles becomes smoother. As a result, it is inferred that the fluidity of the molding resin composition is further improved.
[0109] The material of the core layer is not particularly limited, and examples thereof include (meth)acrylic polymers, olefin polymers, styrene polymers, and urethane polymers.
[0110] The material of the shell layer is not particularly limited, and examples thereof include (meth)acrylic resins and styrene resins.
[0111] The average particle size of the porous polymer particles may be 1 μm to 15 μm, 3 μm to 12 μm, or 5 μm to 10 μm.
[0112] The average particle size of the porous polymer particles may be a value measured as a volume average particle size (D50) using a laser diffraction scattering particle size distribution measuring apparatus, or may be the arithmetic mean of the particle sizes of 100 porous polymer particles randomly selected by cross-section observation of a composition, a cured product, etc. using a SEM (scanning electron microscope).
[0113] The porous polymer particles are preferably thermosetting. Since the porous polymer has thermosetting properties, the porous polymer self-reacts and expands when heated, so that the dimensional change of the molded product including the molding resin composition before and after curing becomes small. As a result, there is a tendency to reduce the warping of the electronic component device including the cured product of the molding resin composition.
[0114] The porous polymer particles may be hollow particles. In the case where the porous polymer particles are hollow particles, the hollowness of the porous polymer particles is preferably 30% to 70%, and more preferably 40% to 60%, from the viewpoint of the balance between low dielectric constant, mixing property and fluidity. For example, when the hollowness of the porous polymer particles is 30% or more, there is a tendency that the dielectric constant of the cured product is reduced. When the hollowness of the porous polymer particles is 70% or less, there is a tendency that the mixing property and fluidity of the molding resin composition are excellent.
[0115] The hollow ratio can be measured by the following method.
[0116] When the hollow particles are observed with a transmission electron microscope, solid parts and hollow parts with different contrasts are observed. The length of each part of the hollow particle toward the center is measured, and the volume is calculated from the value to find the hollowness.
[0117] From the viewpoint of low relative dielectric constant and high fracture energy of the cured product, the content of the porous polymer particles is preferably 5% to 50% by volume, more preferably 8% to 40% by volume, and still more preferably 10% to 30% by volume relative to the total amount of the inorganic filler and the porous polymer particles.
[0118] From the viewpoint of low dielectric loss tangent and high fracture energy of the cured product, the content of the porous polymer particles is preferably 3% to 40% by volume, more preferably 5% to 30% by volume, and even more preferably 8% to 20% by volume relative to the total amount of the molding resin composition.
[0119] [Various additives]
[0120] The molding resin composition of the present disclosure may also include, or may not include, various additives such as a curing accelerator, a coupling agent, an ion exchanger, a release agent, a flame retardant, a colorant, and a stress relaxant, in addition to the above-mentioned components. The molding resin composition of the present disclosure may also include, as necessary, various additives well known in the art, in addition to the additives exemplified below.
[0121] (hardening accelerator)
[0122] The molding resin composition disclosed herein may also include a hardening accelerator. The type of hardening accelerator is not particularly limited and can be selected according to the type of epoxy resin, the desired properties of the molding resin composition, etc. The hardening accelerator can be used alone or in combination of two or more. Specific examples of hardening accelerators are described below, but are not limited to these.
[0123] Examples of the curing accelerator include diazabicycloolefins such as 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), and cyclic amidine compounds such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole; derivatives of the cyclic amidine compounds; phenol novolac salts of the cyclic amidine compounds or their derivatives; and Compounds with intramolecular polarization formed by adding maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone and other quinone compounds, compounds having π bonds such as diazonium methane; cyclic amidinium compounds such as tetraphenylborate of DBU, tetraphenylborate of DBN, tetraphenylborate of 2-ethyl-4-methylimidazole, tetraphenylborate of N-methylmorpholine; pyridine, triethylamine, triethylenediamine, benzyldimethylamine, triethylamine tertiary amine compounds such as alcoholamine, dimethylaminoethanol, tris (dimethylaminomethyl) phenol; derivatives of the tertiary amine compounds; ammonium salt compounds such as tetra-n-butylammonium acetate, tetra-n-butylammonium phosphate, tetraethylammonium acetate, tetra-n-hexylammonium benzoate, and tetrapropylammonium hydroxide; primary phosphines such as ethylphosphine and phenylphosphine, secondary phosphines such as dimethylphosphine and diphenylphosphine, triphenylphosphine, diphenyl (p-toluene) phosphine, tri (alkylphenyl) phosphine, tri (alkoxyphenyl) phosphine, tri (alkylalkoxyphenyl) phosphine, tri (dialkylphenyl) phosphine, tri (trialkylphenyl) phosphine, tri (tetraalkylphenyl) phosphine, tri (dialkoxyphenyl) phosphine, tri (trialkoxyphenyl) phosphine, tri (tetraalkoxyphenyl) phosphine, trialkyl phosphine, dialkyl aryl phosphine, alkyl diaryl phosphine, trinaphthyl phosphine, tri(benzyl) phosphine and other tertiary phosphine; phosphine compounds such as complexes of the organic phosphine and organic boron; compounds with intramolecular polarization formed by adding the organic phosphine or the phosphine compound to maleic anhydride, 1,4-benzoquinone, 2,5-toluoquinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, 2,3-dimethoxy-1,4-benzoquinone, phenyl-1,4-benzoquinone, anthraquinone and other quinone compounds, and compounds having π bonds such as diazonophenylmethane;The organic phosphine or the phosphine compound is reacted with 4-bromophenol, 3-bromophenol, 2-bromophenol, 4-chlorophenol, 3-chlorophenol, 2-chlorophenol, 4-iodophenol, 3-iodophenol, 2-iodophenol, 4-bromo-2-methylphenol, 4-bromo-3-methylphenol, 4-bromo-2,6-dimethylphenol, 4-bromo-3,5-dimethylphenol, 4-bromo-2,6-di-tert-butylphenol, 4-chloro-1-naphthol, 1 Compounds with intramolecular polarization obtained by reacting halogenated phenol compounds such as bromo-2-naphthol, 6-bromo-2-naphthol, 4-bromo-4'-hydroxybiphenyl and then undergoing a dehydrohalogenation process; tetraphenyl phosphonium and other tetrasubstituted phosphoniums, tetraphenyl phosphonium tetra-p-toluene borate and other tetraphenyl borate of tetrasubstituted phosphoniums; tetrasubstituted phosphonium compounds such as salts of tetrasubstituted phosphonium and phenol compounds; phosphate betaine compounds; adducts of phosphonium compounds and silane compounds, etc.;
[0124] Examples of suitable hardening accelerators include triphenylphosphine and quinone compound adducts of triphenylphosphine.
[0125] When the molding resin composition contains a curing accelerator, the content of the curing accelerator is preferably 0.1 to 8 parts by mass, more preferably 0.3 to 7 parts by mass, and even more preferably 0.5 to 6 parts by mass, relative to 100 parts by mass of the total amount of the epoxy resin and the curing agent. By setting the content of the curing accelerator within the above numerical range, the curing speed of the molding resin composition disclosed in the present invention becomes an appropriate value, and the production of the molded product becomes easy.
[0126] (Coupling agent)
[0127] The molding resin composition disclosed herein may include a coupling agent. From the viewpoint of improving the adhesion between the epoxy resin and the hardener and the inorganic filler, the molding resin composition preferably includes a coupling agent. As the coupling agent, there can be cited: silane compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureide silane, vinyl silane, disilazane, titanium compounds, aluminum chelate compounds, aluminum / zirconium compounds and other known coupling agents.
[0128] When the molding resin composition includes a coupling agent, the amount of the coupling agent is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 2.5 parts by mass, relative to 100 parts by mass of the inorganic filler. If the amount of the coupling agent is 0.05 parts by mass or more relative to 100 parts by mass of the inorganic filler, there is a tendency for the adhesion to be further improved. If the amount of the coupling agent is 5 parts by mass or less relative to 100 parts by mass of the inorganic filler, there is a tendency for the moldability of the package to be further improved.
[0129] (Ion Exchanger)
[0130] The molding resin composition disclosed in the present invention may also contain an ion exchanger. From the viewpoint of improving the moisture resistance and high temperature storage characteristics of the electronic component device including the sealed electronic component, the molding resin composition preferably contains an ion exchanger. There is no particular limitation on the ion exchanger, and previously known ones can be used. Specifically, hydrotalcite compounds and hydroxides containing at least one element selected from the group consisting of magnesium, aluminum, titanium, zirconium and bismuth can be listed. The ion exchanger can be used alone or in combination of two or more. Among them, the hydrotalcite represented by the following general formula (A) is preferred.
[0131] Mg (1-X) Al X (OH)2(CO3) X / 2 ·mH2O……(A)
[0132] (0<X≦0.5, m is a positive number)
[0133] When the molding resin composition contains an ion exchanger, the content thereof is not particularly limited as long as it is a sufficient amount for capturing ions such as halogen ions. For example, the content of the ion exchanger is preferably 0.1 to 30 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0134] (Release Agent)
[0135] From the viewpoint of obtaining good demolding properties from the mold during molding, the molding resin composition disclosed in the present invention may also include a mold release agent. The mold release agent is not particularly limited, and previously known ones can be used. Specifically, ester waxes such as palm wax, montanic acid, stearic acid and other higher fatty acids, higher fatty acid metal salts, montanic acid esters, oxidized polyethylene, non-oxidized polyethylene and other polyolefin waxes, etc. can be listed. The mold release agent can be used alone or in combination of two or more.
[0136] When the molding resin composition includes a release agent, the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the resin component. If the amount of the release agent is 0.01 parts by mass or more relative to 100 parts by mass of the resin component, there is a tendency to fully obtain demoulding properties. If the amount of the release agent is 10 parts by mass or less relative to 100 parts by mass of the resin component, there is a tendency to obtain better adhesion.
[0137] (Flame Retardant)
[0138] The molding resin composition disclosed herein may also contain a flame retardant. The flame retardant is not particularly limited, and previously known ones can be used. Specifically, organic compounds or inorganic compounds containing halogen atoms, antimony atoms, nitrogen atoms, or phosphorus atoms, metal hydroxides, etc. can be cited. The flame retardant can be used alone or in combination of two or more.
[0139] When the molding resin composition contains a flame retardant, the amount thereof is not particularly limited as long as it is a sufficient amount to obtain the desired flame retardant effect. For example, the amount of the flame retardant is preferably 1 to 30 parts by mass, and more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the total of the epoxy resin and the hardener.
[0140] (Colorant)
[0141] The molding resin composition disclosed herein may also contain a colorant. As the colorant, known colorants such as carbon black, organic dyes, organic pigments, titanium oxide, red lead, and iron oxide may be cited. The content of the colorant may be appropriately selected according to the purpose, etc. The colorant may be used alone or in combination of two or more.
[0142] (Stress Relaxant)
[0143] The molding resin composition disclosed in the present invention may contain a stress relaxant. By including a stress relaxant, the warping deformation of the package and the generation of package cracks can be further reduced. As a stress relaxant, commonly used known stress relaxants (flexible agents) can be cited. Specifically, thermoplastic elastomers such as silicone, styrene, olefin, urethane, polyester, polyether, polyamide, and polybutadiene can be cited; indene-styrene-coumarone copolymers, etc.; organic phosphorus compounds such as triphenylphosphine oxide and phosphate; natural rubber (natural rubber, NR), acrylonitrile butadiene rubber (acrylonitrile butadiene rubber, NBR), acrylic rubber, urethane rubber, silicone powder and other rubber particles; methyl methacrylate-styrene-butadiene copolymer (methacrylate methyl styrenebutadiene, MBS), methyl methacrylate-silicone copolymer, methyl methacrylate-butyl acrylate copolymer and other rubber particles with core-shell structure. The stress relaxant can be used alone or in combination of two or more.
[0144] Examples of the silicone-based stress relaxant include silicone-based stress relaxants having an epoxy group, silicone-based stress relaxants having an amino group, and silicone-based stress relaxants obtained by polyether-modifying these. Silicone compounds such as silicone compounds having an epoxy group and polyether silicone compounds are more preferred.
[0145] From the viewpoint of dielectric loss tangent, the stress relaxation agent preferably includes at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide.
[0146] When the molding resin composition contains a stress relaxation agent, the amount thereof is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the total of the epoxy resin and the curing agent.
[0147] When the stress relaxer contains at least one of an indene-styrene-coumarone copolymer and triphenylphosphine oxide, the amount thereof is, for example, preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, based on 100 parts by mass of the total of the epoxy resin and the hardener.
[0148] The content of the silicone-based stress relaxant may be, for example, 2 parts by mass or less, or 1 part by mass or less, relative to 100 parts by mass of the total of the epoxy resin and the hardener. The molding resin composition may not contain the silicone-based stress relaxant. The lower limit of the content of the silicone-based stress relaxant is not particularly limited, and may be 0 parts by mass or 0.1 parts by mass.
[0149] From the viewpoint of dielectric loss tangent, the content of the silicone-based stress relaxation agent is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, particularly preferably 5% by mass or less, and extremely preferably 0.5% by mass or less, relative to the total amount of the molding resin composition. The lower limit of the content of the silicone-based stress relaxation agent is not particularly limited, and may be 0% by mass or 0.1% by mass.
[0150] (Method for preparing molding resin composition)
[0151] The preparation method of the molding resin composition is not particularly limited. As a general method, the following method can be cited: after the components of the specified blending amount are fully mixed by a mixer, etc., melt-kneading is performed by a grinding roll, an extruder, etc., and then cooled and crushed. More specifically, for example, the following method can be cited: the specified amount of the components is stirred and mixed, and kneaded by a kneader, a roll, an extruder, etc. preheated to 70°C to 140°C, and then cooled and crushed.
[0152] The molding resin composition disclosed in the present invention is preferably solid at normal temperature and pressure (for example, 25° C., atmospheric pressure). The shape of the molding resin composition when it is solid is not particularly limited, and powder, granular, sheet, etc. can be cited. From the perspective of operability, the size and mass of the molding resin composition when it is in sheet form are preferably the size and mass that match the molding conditions of the package.
[0153] (Application of molding resin composition)
[0154] The molding resin composition disclosed herein can be applied to, for example, electronic component devices described below, and particularly to the production of high-frequency devices. The molding resin composition disclosed herein can also be used to seal electronic components in high-frequency devices.
[0155] In particular, in recent years, with the popularization of the fifth-generation mobile communication system (5G), the high-functionality and miniaturization of semiconductor packages (PKG) used for electronic parts devices have continued to develop. Moreover, with the miniaturization and high-functionality of PKG, the development of packaged antennas (Antenna in Package, AiP) as PKGs with antenna functions is also underway. In AiP, in order to cope with the increase in the number of channels accompanied by the diversification of information, the radio waves used in communication are high-frequency, and a low dielectric loss tangent is required in the sealing material.
[0156] As described above, the molding resin composition of the present disclosure can obtain a cured product having a low dielectric loss tangent. Therefore, among high-frequency devices, it is particularly suitable for antenna-in-package (AiP) applications in which an antenna disposed on a supporting member is sealed with the molding resin composition.
[0157] In an electronic component device including an antenna such as a package antenna, when an amplifier for power supply is provided on the side opposite to the antenna, heat is generated due to power supply. From the viewpoint of improving heat dissipation, the molding resin composition used in the manufacture of the electronic component device preferably contains alumina particles as an inorganic filler.
[0158] <Electronic components and devices>
[0159] The electronic component device disclosed herein includes a supporting member, an electronic component disposed on the supporting member, and a cured product of the molding resin composition that seals the electronic component.
[0160] As electronic component devices, there can be listed those in which electronic components (active components such as semiconductor chips, transistors, diodes, thyristors, etc., passive components such as capacitors, resistors, coils, antennas, etc.) are mounted on support members such as lead frames, conveyor tapes with completed wiring, wiring boards, glass, silicon wafers, organic substrates, and the electronic component area is sealed with a molding resin composition (for example, high-frequency devices).
[0161] The type of the supporting member is not particularly limited, and a supporting member generally used in the manufacture of electronic component devices can be used.
[0162] The electronic component may include an antenna, or may include an antenna and an element other than an antenna. The antenna is not limited as long as it functions as an antenna, and may be an antenna element or wiring.
[0163] In addition, in the electronic component device of the present disclosure, other electronic components may be arranged on the surface of the support member opposite to the surface on which the electronic components are arranged, as needed. Other electronic components may be sealed by the molding resin composition, may be sealed by other resin compositions, or may not be sealed.
[0164] (Method for manufacturing electronic component device)
[0165] The method for manufacturing an electronic component device disclosed herein includes: a step of arranging an electronic component on a supporting member; and a step of sealing the electronic component with the molding resin composition.
[0166] The method for implementing each of the steps is not particularly limited, and can be carried out by a general method. In addition, the types of support members and electronic components used in the manufacture of electronic component devices are not particularly limited, and support members and electronic components commonly used in the manufacture of electronic component devices can be used.
[0167] Examples of methods for sealing electronic components using the molding resin composition include low-pressure transfer molding, injection molding, compression molding, etc. Among these, the low-pressure transfer molding method is generally used.
[0168] Example
[0169] Hereinafter, the embodiment will be described in detail by way of examples, but the scope of the embodiment is not limited to these examples.
[0170] <Preparation of molding resin composition>
[0171] The molding resin compositions of Examples and Comparative Examples were prepared by mixing the following components in the blending ratios (parts by mass) shown in Table 1. The molding resin compositions are solid at normal temperature and pressure.
[0172] In addition, in Table 1, "-" means that the said component is not contained.
[0173] In addition, the filler in Table 1 means the total of the inorganic filler and the porous polymer.
[0174] Epoxy resin 1: biphenyl type epoxy resin, epoxy equivalent 192g / eq
[0175] Epoxy resin 2: triphenylmethane type epoxy resin, epoxy equivalent 169g / eq
[0176] Epoxy resin 3: o-cresol novolac type epoxy resin, epoxy equivalent 200g / eq
[0177] Hardener: Active ester compound, DIC Co., Ltd., product name "EXB-8", ester equivalent 213g / eq
[0178] Hardening accelerator: adduct of tributylphosphine and 1,4-benzoquinone
[0179] · Coupling agent 1: 3-glycidyloxypropyltrimethoxysilane
[0180] · Coupling agent 2: N-phenyl-3-aminopropyltrimethoxysilane
[0181] Colorant: Carbon black
[0182] Filler 1: Silica powder as an inorganic filler, with a volume average particle size of 0.5 μm and a specific gravity of 2.2 g / cm 3
[0183] Filler 2: Silica powder as an inorganic filler, with a volume average particle size of 4.0 μm and a specific gravity of 2.2 g / cm 3
[0184] Filler 3: Polymethyl methacrylate particles as porous polymer particles, volume average particle size 8 μm, maximum particle size 20 μm, spherical, thermal decomposition temperature 265°C, hollow ratio 45%, specific gravity 0.6 g / cm 3
[0185] Filler 4: Acrylic urethane polymer particles as porous polymer particles, volume average particle size 6 μm, spherical, thermal decomposition temperature 280°C, specific gravity 0.6 g / cm 3
[0186] Filler 5: Porous polymer particles with a shell layer (material: styrene resin), low oil absorption, volume average particle size 7 μm, maximum particle size 20 μm, spherical, thermal decomposition temperature 280°C, hollow ratio 45%, specific gravity 0.6 g / cm 3
[0187] Filler 6: Porous polymer particles with a shell layer (material: styrene resin), low oil absorption, volume average particle size 7.5 μm, maximum particle size 20 μm, spherical, thermal decomposition temperature 290°C, hollow ratio 50%, specific gravity 0.6 g / cm 3
[0188] In addition, the volume average particle size of each of the inorganic fillers is a value obtained by the following measurement.
[0189] Specifically, first, an inorganic filler is added to a dispersion medium (water) in a range of 0.01 mass % to 0.1 mass %, and the mixture is dispersed for 5 minutes using a bath type ultrasonic cleaning machine.
[0190] 5 ml of the obtained dispersion was poured into a tank, and the particle size distribution was measured at 25°C using a laser diffraction scattering particle size distribution measuring apparatus (Horiba, Ltd., LA920).
[0191] The particle diameter of the cumulative value of 50% (volume basis) in the obtained particle size distribution was defined as the volume average particle diameter.
[0192] (Evaluation of spiral flow (SF))
[0193] The molding resin composition was molded by a transfer molding machine using a spiral flow measurement mold in accordance with EMMI-1-66 at a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds, and the flow distance (cm) was determined. The results are shown in Table 1.
[0194] (Room temperature bending test)
[0195] The molding resin composition was loaded into a transfer molding machine and molded under the conditions of a mold temperature of 175°C, a molding pressure of 6.9 MPa, and a curing time of 120 seconds. Post-curing was performed at 175°C for 6 hours to produce a rectangular test piece of 127 mm × 12.7 mm × 4 mm.
[0196] Tensilon (A&D Co.) was used as an evaluation device. A three-point support bending test according to JIS-K-7171 (2016) was performed at room temperature (25°C). The bending elastic modulus E, bending strength S, and breaking elongation ε of the test piece were calculated using the following formulas.
[0197] The flexural modulus E (GPa), the flexural strength S (MPa), and the elongation at break ε (%) are defined by the following formulae.
[0198] In the following formula, P is the value of the force gauge (N), y is the displacement (mm), l is the span = 64 mm, w is the test piece width = 12.7 mm, and h is the test piece thickness = 4 mm. The subscript max indicates the maximum value. Regarding the bending elastic coefficient E, the value calculated using the formula described below is converted into GPa.
[0199] [Number 1]
[0200]
[0201] [Number 2]
[0202]
[0203] [Number 3]
[0204]
[0205] (Determination of fracture energy)
[0206] The molding resin composition was subjected to the above-mentioned bending test, and the area of the SS curve of the elongation at break (%) and the bending strength (MPa) were calculated by the following formula, and the values were defined as the breaking energy. Figure 1 SS curves of the elongation at break and the flexural strength obtained using the molding resin compositions of the examples and comparative examples are shown in FIG.
[0207] Table 1 shows the results.
[0208] [Number 4]
[0209]
[0210] σ = flexural strength ε = elongation at break
[0211] (Molding shrinkage measurement)
[0212] The molding resin composition was molded using a transfer molding machine at a molding temperature of 175° C., a molding pressure of 6.9 MPa, and a curing time of 120 seconds to obtain a plate-shaped molded product (127 mm in length, 12.7 mm in width, and 6.4 mm in thickness).
[0213] The molding shrinkage A (%) (molding shrinkage AM in Table 1) was calculated by the following formula from the length D of the mold cavity at 25°C and the length d of the molded product at room temperature (25°C) measured in advance.
[0214] Molding shrinkage A (%) = ((Dd) / D) × 100
[0215] The molding resin composition was molded using a transfer molding machine at a molding temperature of 175° C., a molding pressure of 6.9 MPa, and a curing time of 120 seconds to obtain a plate-shaped molded product (127 mm in length, 12.7 mm in width, and 6.4 mm in thickness). The molded product was post-cured at 175° C. for 5 hours to obtain a plate-shaped cured product.
[0216] The molding shrinkage B (%) (molding shrinkage AC in Table 1) was calculated by the following formula from the previously measured length D of the mold cavity at 25°C and the length d of the cured product at room temperature (25°C).
[0217] Molding shrinkage B (%) = ((Dd) / D) × 100
[0218] (Determination of relative dielectric constant and dielectric loss tangent)
[0219] The sealing resin composition was loaded into a transfer molding machine, molded under the conditions of a mold temperature of 180°C, a molding pressure of 6.9 MPa, and a curing time of 90 seconds, and post-cured at 175°C for 6 hours to obtain a rod-shaped cured product (90 mm in length, 0.6 mm in width, and 0.8 mm in thickness). The cured product was used as a test piece, and the relative dielectric constant (Dk) and dielectric loss tangent (Df) at 10 GHz were measured at a temperature of 25±3°C using a cavity resonator (Kanto Electronics Application Development Co., Ltd.) and a network analyzer (Keysight Technologies, product name "PNAE8364B").
[0220] The models of the cavity resonators used are as follows.
[0221] 10GHz···CP531
[0222] [Table 1]
[0223]
[0224] As is clear from the evaluation results in Table 1, the cured products of the molding resin compositions of Examples 1 and 2 have lower relative dielectric constants than the cured product of the molding resin composition of Comparative Example 1 using the same type of epoxy resin.
[0225] The cured products of the molding resin compositions of Examples 3 to 6 have a lower relative dielectric constant than the cured product of the molding resin composition of Comparative Example 2 using the same type of epoxy resin. Furthermore, in Examples 4 to 6, it was confirmed that the molding shrinkage after curing decreases as the amount of the filler 5, which is the porous polymer particles, increases.
[0226] (Confirmation of changes in viscoelastic properties due to heating)
[0227] The viscoelasticity of the filler 5 was measured in the state of being unheated (0h), heated at 175°C for 5 minutes, 2 hours or 6 hours. For the viscoelasticity measurement, test samples were prepared in the state of being unheated (0h), heated at 175°C for 5 minutes, 2 hours or 6 hours, and the measurement was performed using a rotational rheometer Kinexus lab+ (manufactured by NETZSCH Japan Co., Ltd.) under the conditions of amplitude method, strain (Strain) = 0.1%, frequency = 1Hz, GAP = 0.5mm, measurement temperature range 25°C to 180°C, and heating rate 10°C / min. The results are shown in Figure 2 middle. Figure 2 1.00E+0X (X is an integer) means 10 X (10 to the power of X).
[0228] like Figure 2 As shown, the sample after heating the composition has a high elastic modulus at the measurement temperature. Based on the above results, it is estimated that the filler 5 has self-reactivity caused by heating (ie, thermal curing).
[0229] The entire contents of the disclosure of Japanese Patent Application No. 2022-188706 filed on November 25, 2022 are incorporated into this specification by reference.
[0230] All documents, patent applications, and technical specifications described in this specification are incorporated herein by reference to the same extent as if each document, patent application, or technical specification was specifically and individually described as being incorporated by reference.
Claims
1. A molding resin composition comprising: an epoxy resin; a hardener comprising an active ester compound; an inorganic filler; and porous polymer particles.
2. The molding resin composition according to claim 1, wherein The porous polymer particle includes a core portion having a porous shape and a shell portion covering at least a portion of the core portion.
3. The molding resin composition according to claim 1, wherein The porous polymer particles include a core having a porous shape, and the core includes at least one polymer selected from the group consisting of a (meth)acrylic polymer, an olefin polymer, a styrene polymer, and a urethane polymer.
4. The molding resin composition according to claim 1, wherein The content of the porous polymer particles is 5% to 50% by volume based on the total amount of the inorganic filler and the porous polymer particles.
5. The molding resin composition according to claim 1, wherein The content of the porous polymer particles is 3% to 40% by volume based on the total amount of the molding resin composition.
6. The molding resin composition according to claim 1, wherein The porous polymer particles are thermosetting.
7. The molding resin composition according to any one of claims 1 to 6, which is used for a high-frequency device.
8. The molding resin composition according to claim 7, which is used for sealing electronic parts in high-frequency devices.
9. The molding resin composition according to claim 7, which is used for encapsulating an antenna.
10. An electronic component device comprising: Supporting members; Electronic components are arranged on the supporting member; as well as A cured product of the molding resin composition according to any one of claims 1 to 9 for sealing the electronic component.
11. The electronic component device according to claim 10, wherein: The electronic component includes an antenna.
